Architexture for Engaged Pedagogy: How Classroom Design Affects the Teaching and Learning of English Literature - Oshanthaka Cabraal (The Open University of Sri Lanka, 2022)
English Literature as a subject challenges the traditional notion of accuracy and demands negotiation between teachers and learners. It is a discipline that requires discussion, innovation and enquiry. Therefore, teaching and learning English Literature requires an environment that facilitates and accommodates engaging pedagogies as opposed to classrooms which exercise authority. Studies have shown that engaging pedagogies are enhanced within classrooms that are designed to encourage modern pedagogic practices. However, an often overlooked area of Sri Lankan schools is the effect classroom design has on learning and teaching. This in particular affects English Literature due to its engaging pedagogic practices. This study aims to evaluate and understand classroom designs that help maintain engaging pedagogies for English Literature and the effect classroom design has on student learning. Data for the present study were collected through a lesson observation as well as semi-structured interviews of learners and a teacher of Advanced Level English Literature. Additionally, the school library was observed and discussed to understand the effects of learning environments on student learning. Through deductive data analysis, this study analyses features that contribute to the culture of learning required for Advanced Level English Literature. The implications of this study highlight that classroom design and culture promote learner thinking and collaboration. These factors enhance the learning experience of English Literature as they instill democratic values among learners and encourage learner participation.